LABORATORY+REARED ZOEAE AND MEGALOPA OF THE MANGROVE CRAB SESARMA BROCKII DE MAN - Vijayakumaran, G; Kannupandi, T (Indian Journal of Fisheries, 2011)
Four zoeal stages. and one megalopa stage of the mangrove crab Sesarmabrockii de Man obtained; as a result of laboratory rearing from a berried mothercollected and maintained from the wild are described and illustrated. The larvalcharacters are also comj>ared at length with those of two other Indian species,S. tetragoniim and S. lanatum.